Osteoarticular allograft reconstruction of post-traumatic defect of distal femur in a pediatric patient: A case report and literature review. Issue 11 (November 2016) - Borade, Amrut; Kempegowda, Harish; Fernandez, Meagan; Horwitz, Daniel S.
Abstract: Successful results of osteoarticular allografts in reconstruction of periarticular bone defect after tumor resection encouraged its utilization in post-traumatic defects. Here we describe a case of post-traumatic skeletal defect in a 4 year-old girl treated with osteoarticular allograft reconstruction. Due to severity of the associated soft tissue injury and contamination at presentation staged treatment with antibiotic spacer followed by the reconstruction was carried out. At the end of one year the patient achieved 'Musculoskeletal tumor society' functional score of 27 points and radiographic score of 93%. Reconstruction immediately after healing of soft tissues prevented development of any varus or valgus deformity of the knee. Our case demonstrates utility of osteoarticular allograft in a pediatric post-traumatic skeletal defect.